The Therapy Box in the Classroom: A Function-based Multi-Component Directive Play Therapy Treatment Package Intervention - Susan E Elswick; Melissa Hirschi; Maria Elena Delavega; Laura B Casey (International Journal of School Social Work, 2020)
The Therapy Box is a behavioral intervention being researched to determine its effectiveness as a Response to Intervention (RtI) Tier 2 and Tier 3 behavioral intervention for identified students. The Therapy Box assists students with developing self-regulatory skills and increasing their social-emotional literacy while providing a supportive, caring, and safe classroom environment. The Therapy Box is a treatment package that encompasses the theories of Cognitive Behavioral Therapy (CBT), the use of functional behavior assessments, B.F. Skinner's theory of manding, Differential Reinforcement of Alternative Behavior (DRA), and Directive Play Therapy. The hypothesis is that the student will be able to mand for "calm down time" with the box in lieu of an anger outburst/ episode within the classroom. The Therapy Box must be explained, and the student is part of the box creation during directive play therapy sessions. The intervention includes both student and teacher support to ensure skill generalization and successful outcomes. This research indicates that The Therapy Box proves to be an effective behavioral intervention for at- risk students.
Keywords: aggression; RtI; classroom management; positive behavior support